2000
DOI: 10.1002/1529-0131(200010)43:10<2169::aid-anr4>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of taurine chloramine inhibition of cytokine (interleukin‐6, interleukin‐8) production by rheumatoid arthritis fibroblast‐like synoviocytes

Abstract: Tau-Cl inhibition of IL-6 and IL-8 synthesis in FLS from RA patients results from the ability of this compound to diminish the activity of the major transcriptional regulators (NF-kappaB and AP-1), which subsequently reduces the transcription of these cytokine genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(52 citation statements)
references
References 47 publications
1
48
0
1
Order By: Relevance
“…22,[24][25][26] Taurine is also known to have potent antioxidant properties and to regulate proinflammatory cytokines. [27][28][29] Although taurine has proven effective for treating alcohol-induced hepatic injury, 30 the precise signaling involved in its protective activity is still unclear. This study further showed that by inhibiting TLR-4/ MyD88 and IjB/NFjB p65 signaling, taurine suppresses inflammation-associated proteins and cytokines, which alleviates chronic alcohol-induced liver inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…22,[24][25][26] Taurine is also known to have potent antioxidant properties and to regulate proinflammatory cytokines. [27][28][29] Although taurine has proven effective for treating alcohol-induced hepatic injury, 30 the precise signaling involved in its protective activity is still unclear. This study further showed that by inhibiting TLR-4/ MyD88 and IjB/NFjB p65 signaling, taurine suppresses inflammation-associated proteins and cytokines, which alleviates chronic alcohol-induced liver inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…After 18 h of treatment, total RNA was prepared and transcribed into complementary DNA (cDNA) as described previously [26]. The selection of this optimal time point for RNA analysis was based on preliminary time course (6-24 h) experiments.…”
Section: Reverse Transcriptase-polymerase Chain Reaction (Rt-pcr)mentioning
confidence: 99%
“…It is possible that the blockade of RA FLS cell-cycle progression may represent novel therapeutic approach for RA treatment. We have previously found that taurine chloramine (Tau-Cl), a physiologic compound of known anti-infl ammatory activities, inhibits not only some pro-infl ammatory functions of RA FLS [25][26][27][28][29] but also proliferation of these cells [25,29]. Taurine chloramine is generated by activated neutrophils in a reaction of hypochlorous acid (HOCl) with b-amino acid taurine (Tau) [30].…”
Section: Introductionmentioning
confidence: 99%
“…36) or IL-15DM/Fc␥1 (human Fc␥1), a high-affinity receptor site-specific antagonist for IL-15R␣-chain protein (both from Cardion Pharmaceuticals, Boston, MA); 2) relevant isotype controls, murine IgG2a or human IgG1, respectively (both Abs from R&D Systems); 3) goat anti-human IL-15 neutralizing Ab (5 g/ml); or 4) control total goat IgG (both Abs from R&D Systems). After 24 h, one-third of the culture medium was discarded and fresh medium with supplementary proteins were added for another 24 h. Total RNA extraction, cDNA template preparation, and the RT-PCR were done as previously described (37). Quantitative competitive RT-PCR was used to measure bcl-2, bcl-x L , and GAPDH mRNA expression.…”
Section: Expression Of Mrna-encoding Il-15 Il-15r␣ Il-2/il-15r␤ Ilmentioning
confidence: 99%